Anisotropy of the effective Lande factor in AlxGa1-x As parabolic quantum wells under applied magnetic fields - Bruno-Alfonso, A. [UNESP]; Raigoza, N.; Reyes-Gomez, E. (Elsevier B.V., 2010)
The anisotropy of the effective Lande factor in Al(x)Gal(1-x)As parabolic quantum wells under magnetic fields is theoretically investigated. The non-parabolicity and anisotropy of the conduction band are taken into account through the Ogg-McCombe Hamiltonian together with the cubic Dresselhaus spin-orbit term. The calculated effective g factor is larger when the magnetic field is applied along the growth direction. As the well widens, its anisotropy increases sharply and then decreases slowly. For the considered field strengths, the anisotropy is maximum for a well width similar to 50 angstrom. Moreover, this anisotropy increases with the field strength and the maximum value of the aluminum concentration within the quantum well. (C) 2010 Elsevier B.V. All rights reserved.